Reversible Polarization Rotation in Epitaxial Ferroelectric Bilayers. Issue 18 (22nd July 2016) - Liu, Guangqing; Zhang, Qi; Huang, Hsin‐Hui; Munroe, Paul; Nagarajan, Valanoor; Simons, Hugh; Hong, Zijian; Chen, Long‐Qing
Abstract : Polarization rotation engineering is a promising path to giant dielectric and electromechanical responses in ferroelectric materials and devices. This work demonstrates robust and reversible in‐ to out‐of‐plane polarization rotation in ultrathin (nanoscale) epitaxial (001) tetragonal PbZr0.3 Ti0.7 O3 (PZT‐T)/rhombohedral PbZr0.55 Ti0.45 O3 (PZT‐R) ferroelectric bilayers. An underlying 20 nm thick PZT‐R layer reduces the symmetry in a 5 nm thick PZT‐T layer by imposing an in‐plane tensile strain while simultaneously decoupling the PZT‐T layer from the substrate. This prevents clamping and facilitates large‐scale polarization rotation switching (≈60 μC cm −2 ) and an effective d 33 response 500% (≈250 pm V −1 ) larger than the PZT‐R layer alone. Furthermore, this enhancement is stable for more than 10 7 electrical switching cycles. These bilayers present a simple and highly controllable means to design and optimize rotational polar systems as an alternate to traditional composition‐based approaches. The precise control of the subtle interface‐driven interactions between the lattice and the external factors that control polarization opens a new door to enhanced—or completely new—functional properties. Abstract : Reversible polarization rotation has been achieved in ultrathin epitaxial 5 nm tetragonal PbZr0.3 Ti0.7 O3 (PZT‐T)/20 nm rhombohedral PbZr0.55 Ti0.45 O3 (PZT‐R) bilayer films. The underlying 20 nm PZT‐R layer reduces the symmetry in the top 5 nm PZT‐T layer by imposing an in‐plane tensile strain while preventing clamping effect. This facilitates large‐scale polarization rotation switching (≈60 μC cm −2 ) and strong electromechanical response ( d 33 ≈ 250 pm V −1 ).